2004
DOI: 10.1111/j.1527-5299.2004.03409.x
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Impedance Cardiography to Determine Cardiac vs. Noncardiac Cause of Dyspnea in the Emergency Department

Abstract: Determining the correct diagnosis of patients with dyspnea can be challenging. Early and accurate determination of the cause of dyspnea is vital in instituting timely and appropriate interventions. Hemodynamic parameters may aid in the evaluation of dyspnea, but are difficult to assess by physical exam. Impedance cardiography (ICG) is a newly validated method of determining hemodynamic parameters noninvasively. The purpose of this study was to determine the accuracy in differentiating cardiac from noncardiac c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 14 publications
0
21
1
1
Order By: Relevance
“…There were no significant changes in any index. .9) 171.9 (9.4) 169.9 (9.0) 175.6 (9.8) 95% CI 153.7,189.4 155.2,183.8 153.8,188.4 153.4,188.0 146.4,183.3 152.9,194.5 155.1,190.1 153.5,190.3 152.3,187.5 156.3,194.9 Daikenchuto + Water Mean (SEM) 165.6 (10.2) 172.6 (10.1) 182.5 (11.3)* 185.2 (11.5)** 188.5 (11.6)** 186.7 (13.2)* 189.7 (13.4)** 189.8 (13.7)** 186.8 (12.9)** 178.3 (11.3) 95% CI 145.6,185.5 152.9,192.3 160.4,204.6 162.8,207.7 165.7,211. culate hemodynamic parameters such as stroke volume, CO, and cardiac index (Springfield et al 2004). The latest-generation ICG device (BioZ ICG Module, Dash 3000 ® , GE Healthcare, Tokyo, Japan) provides highly reproducible and accurate data in a number of clinical settings, including assessment of heart failure (Strobeck and Silver 2004).…”
Section: Discussionmentioning
confidence: 99%
“…There were no significant changes in any index. .9) 171.9 (9.4) 169.9 (9.0) 175.6 (9.8) 95% CI 153.7,189.4 155.2,183.8 153.8,188.4 153.4,188.0 146.4,183.3 152.9,194.5 155.1,190.1 153.5,190.3 152.3,187.5 156.3,194.9 Daikenchuto + Water Mean (SEM) 165.6 (10.2) 172.6 (10.1) 182.5 (11.3)* 185.2 (11.5)** 188.5 (11.6)** 186.7 (13.2)* 189.7 (13.4)** 189.8 (13.7)** 186.8 (12.9)** 178.3 (11.3) 95% CI 145.6,185.5 152.9,192.3 160.4,204.6 162.8,207.7 165.7,211. culate hemodynamic parameters such as stroke volume, CO, and cardiac index (Springfield et al 2004). The latest-generation ICG device (BioZ ICG Module, Dash 3000 ® , GE Healthcare, Tokyo, Japan) provides highly reproducible and accurate data in a number of clinical settings, including assessment of heart failure (Strobeck and Silver 2004).…”
Section: Discussionmentioning
confidence: 99%
“…TIC made physicians change patients' diagnosis in 13% of the cases, and medications in 39% of the patients 6 . In another study, it was useful to differentiate cardiac form noncardiac dyspnea 7 . However, these studies are limited by the lack of a control group and by nonrandomization, which makes it difficult to evaluate the ability of the method in changing outcomes.…”
Section: Villacorta Et Al Impedance In the Assessment Of Cardiac Outputmentioning
confidence: 99%
“…The clinical application of TIC has been assessed in patients with acute dyspnea in the emergency department 6,7 . TIC made physicians change patients' diagnosis in 13% of the cases, and medications in 39% of the patients 6 .…”
Section: Villacorta Et Al Impedance In the Assessment Of Cardiac Outputmentioning
confidence: 99%
See 1 more Smart Citation
“…In another setting, Springfield et al [22] found that thoracic impedance had a sensitivity of 92 % and a sensitivity of 88% for the diagnosis of AHF. These results are not directly comparable to ours because thoracic impedance mainly studies cardiac output and aortic velocity.…”
Section: Discussionmentioning
confidence: 97%